Abusing science. Issue 10 (25th August 2020) - McInerney, Joseph D.; Dougherty, Michael J.
Abstract: The perversion of science in the interest of ideology and greed is not a new phenomenon, but a public that is largely scientifically illiterate now is besieged by "alternative facts" and well‐designed efforts to discredit legitimate science on topics ranging from vaccines to climate change. Here, we examine three topics rooted in biology and biomedicine—creationism, harms from tobacco, and opioid addiction—to show that those purveying misinformation employ a consistent pattern of intellectual dishonesty to delegitimize science that challenges their ideological positions. Individual scientists and the scientific community at large should confront and counter these attacks on the intellectual integrity that is at the heart of the scientific enterprise.